2009
DOI: 10.1038/emboj.2009.67
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-mediated proteolysis of HuR by heat shock

Abstract: The RNA‐binding protein HuR regulates the stability and translation of numerous mRNAs encoding stress‐response and proliferative proteins. Although its post‐transcriptional influence has been linked primarily to its cytoplasmic translocation, here we report that moderate heat shock (HS) potently reduces HuR levels, thereby altering the expression of HuR target mRNAs. HS did not change HuR mRNA levels or de novo translation, but instead reduced HuR protein stability. Supporting the involvement of the ubiquitin–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
154
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(160 citation statements)
references
References 56 publications
(84 reference statements)
5
154
0
1
Order By: Relevance
“…On the basis of an increasing literature establishing a correlation between posttranslational modifications of RBPs and acquisition of new biological properties (22), we next compared HuR phosphorylation status between ALK þ and ALK À cells. Indeed, besides methylation and ubiquitinylation (27,28), HuR has been shown to be phosphorylated on serine and threonine residues in response to proliferation signals or damaging stimuli (26). Thus, phosphorylation of HuR by the serine-threonine kinases cdk1, PKCd, or pKCa has been reported to induce HuR translocation into the cytoplasm and modulate its RNA-binding properties (26).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of an increasing literature establishing a correlation between posttranslational modifications of RBPs and acquisition of new biological properties (22), we next compared HuR phosphorylation status between ALK þ and ALK À cells. Indeed, besides methylation and ubiquitinylation (27,28), HuR has been shown to be phosphorylated on serine and threonine residues in response to proliferation signals or damaging stimuli (26). Thus, phosphorylation of HuR by the serine-threonine kinases cdk1, PKCd, or pKCa has been reported to induce HuR translocation into the cytoplasm and modulate its RNA-binding properties (26).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ubiquitination infl uences the stability of HuR, which is degraded by the ubiquitin-proteasome pathway following a moderate heat shock (95) . Certain classes of RBPsprimarily hnRNPs and serine/arginine-rich (SR) proteins -are site-specifi cally methylated by arginine methy ltransferases (PRMTs) [reviewed in (96) ].…”
Section: Dynamics -Rewiring the Rna-protein Networkmentioning
confidence: 99%
“…It has been demonstrated that phosphorylation at specific serines or a threonine of HuR can lead to altered cellular localization of the protein and, in one case, can increase the RNA-binding affinity of HuR (Doller et al 2010;Srikantan and Gorospe 2012). One report indicated that heat shock induces ubiquitination of HuR at Lys 182, leading to degradation of HuR and decreased levels of HuR target mRNA abundance (Abdelmohsen et al 2009). The HuR proteins have been shown to interact dynamically with their RNA targets in various large mRNPs (Keene 2001;Mukherjee et al 2009;Masuda et al 2011).…”
mentioning
confidence: 99%